Intermittent midline suprasternal neck mass caused by superior herniation of the thymus. (29th September 2014) - Su, Siew Choo; Hess, Thomas; Whybourne, Annie; Chang, Anne B
Abstract Neck masses in infants and children have a wide differential diagnosis. However, neck masses apparent only during raised intrathoracic pressure are rare with a limited number of causes, including superior herniation of the normal thymus, apical lung herniation, jugular phlebectasia and laryngocoele. These conditions can easily be differentiated from one another by imaging. We present an infant with intermittent suprasternal neck mass visible only during increased intrathoracic pressure, produced either by crying or straining. Diagnosis of superior herniation of the thymus into the neck was confirmed by ultrasonography with the characteristic sonographic appearances of the normal thymus as well as its shape, size and location. Ultrasonography should be the first imaging modality of choice. Management of superior herniation of the thymus into the neck should be conservative as the thymus naturally involutes with increasing age. Awareness of the differential diagnosis of neck swelling present only on Vasalva manoeuvre or increased intrathoracic pressure is important to prevent unnecessary tests, avoid radiation, biopsy and surgery.